Desmitis of the straight sesamoidean ligament and avulsion fragments of the proximal eminence of the middle phalanx in a horse imaged by radiographs, ultrasound, CT and MRI. A case report - Brünott, A.; Auriemma, E.; Rijkenhuizen, A. B. M. (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2007)
Objective: Description of the signalment, history, clinical signs and radiological findings of a horse with an acute severe lameness. Radiographs, ultrasonographic, CT and MRI images were taken to visualize the exact lesion. Material and methods: Based upon the history, clinical examination and diagnostic anaesthesia the region of pain was suspected to be the palmar aspect of the pastern joint region. After radiographic and ultrasonographic examination, CT and MRI were performed. A desmitis of the straight distal sesamoidean ligament and avulsion fragments from the proximal eminence of the middle phalanx (middle scutum) were diagnosed. Results: The horse was treated conservatively with oral administration of non-steroidal anti-inflammatory drugs and submitted to a controlled exercise program. Within two weeks significant improvement was evident. After three months the horse had improved both clinically and on the views obtained by ultrasonography. A year later the horse was sound and had returned to his previous athletic level. Conclusion and clinical relevance: This case demonstrates the additional value of CT combined with MRI to a clinical examination and standard diagnostic imaging tools. After clinical, ultrasonographic and radiographic examination the tentative diagnosis was a cyst-like lesion in the proximal region of the pastern joint. The ultrasonographic examination revealed an irregularity in shape and fibre lining of the straight sesamoidean ligament. However, no conclusions were made at this point, since ultrasonography of this region is difficult, and conclusions are hard to be made (4, 6, 7, 9). Arthroscopic diagnostic evaluation of the joint was optional; however, uncertainty remained on the exact localisation of the cyst-like lesion. Based on the CT and MRI it became clear that the horse was suffering of a desmitis of the straight distal sesamoidean ligament and extra-articular avulsion fragments from the proximal border of the middle phalanx. Surgical intervention seemed to be unnecessary, and a conservative treatment was initiated with a successful outcome.
Keywords: Equine; straight distal sesamoidean ligament; magnetic resonance imaging; computed tomography